2001
DOI: 10.1080/713602648
|View full text |Cite
|
Sign up to set email alerts
|

Soluble L-selectin levels during controlled ovarian hyperstimulation

Abstract: We sought to determine whether neutrophil activation, as reflected by soluble L-selectin levels, plays a role in controlled ovarian hyperstimulation (COH) and the possible correlation between soluble L-selectin and serum sex steroid levels. The study population consisted of 14 consecutive patients undergoing our routine in vitro fertilization (IVF) long gonadotropin-releasing hormone (GnRH) analog protocol. Blood was drawn three times during the COH cycle: (1) on the day when adequate suppression was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Since, OHSS almost always develops after hCG administration or in early pregnancy, it was suggested that the hyperstimulated human ovaries produce and secrete factor(s) that cause OHSS, probably by activating a systemic inflammatory response [ 3 , 14 ]. This notion was based on the similarity of VLS to the clinical picture of OHSS [ 3 , 15 ], the significantly higher cytokine concentration in the follicular fluid at the time of oocyte retrieval in patients in whom OHSS subsequently developed [ 4 , 14 , 16 ], and the neutrophil and endothelial activations following hCG administration [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since, OHSS almost always develops after hCG administration or in early pregnancy, it was suggested that the hyperstimulated human ovaries produce and secrete factor(s) that cause OHSS, probably by activating a systemic inflammatory response [ 3 , 14 ]. This notion was based on the similarity of VLS to the clinical picture of OHSS [ 3 , 15 ], the significantly higher cytokine concentration in the follicular fluid at the time of oocyte retrieval in patients in whom OHSS subsequently developed [ 4 , 14 , 16 ], and the neutrophil and endothelial activations following hCG administration [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…μελετών για τη σελεκτίνη ( Orvieto R et al, 2004, Orvieto R et al 2001, Abramov Y et al 2001, Daniel Yair et al 2001)(185),(186),(187),(188) μελετών για τους παράγοντες οξειδωτικού stress (Attaran M. et al 2000, Das S et al 2006, Jana S. et al 2010, Celik E et al 2012) (213), (214),(215),(218) Στις έρευνες σχετικά με τη ρεσιστίνη μελετήθηκαν, 21 υπογόνιμες γυναίκες οι οποίες υποβλήθηκαν σε εξωσωματική γονιμοποίηση με GnRH αγωνιστή στην έρευνα του Seow. (197) Στη μελέτη του Lu συμπεριλήφθηκαν 53 γυναίκες που ακολούθησαν το πρωτόκολλο του αγωνιστή της GnRH.…”
unclassified